2021
DOI: 10.3390/nu13020343
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive Disorders of Pregnancy in Relation to Coffee and Tea Consumption: The Japan Environment and Children’s Study

Abstract: Background: The association between coffee/tea intake and hypertensive disorders of pregnancy (HDP) remains unclear. This study aimed to investigate the association of caffeine, coffee, and tea intake during pregnancy with the risk of HDP. Methods: We assessed this association in 85,533 singleton pregnant women with live births in the Japan Environment and Children’s Study, a prospective cohort in Japan that included women from early pregnancy onward. Caffeinated and decaffeinated coffee and tea (green, oolong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…It has been shown that consumption of caffeinated beverages in the first trimester of pregnancy did not affect the risk of gestational diabetes and gestational hypertension, while in the second trimester it reduced the risk of gestational diabetes (only 1-100 mg caffeine/day; RR = 0.53; 95% CI: 0.35-0.80, up to 200 mg/day -no effect), and did not affect the risk of gestational hypertension. Similar results were obtained in a prospective cohort study of 85533 Japanese women, Kawanishi et al [51]. These authors showed that the consumption of 2-3 cups of coffee/day was associated with a lower risk of hypertension-related pregnancy disorders (OR = 0.79; 95% CI: 0.62-0.99).…”
Section: Metabolic Disorderssupporting
confidence: 84%
“…It has been shown that consumption of caffeinated beverages in the first trimester of pregnancy did not affect the risk of gestational diabetes and gestational hypertension, while in the second trimester it reduced the risk of gestational diabetes (only 1-100 mg caffeine/day; RR = 0.53; 95% CI: 0.35-0.80, up to 200 mg/day -no effect), and did not affect the risk of gestational hypertension. Similar results were obtained in a prospective cohort study of 85533 Japanese women, Kawanishi et al [51]. These authors showed that the consumption of 2-3 cups of coffee/day was associated with a lower risk of hypertension-related pregnancy disorders (OR = 0.79; 95% CI: 0.62-0.99).…”
Section: Metabolic Disorderssupporting
confidence: 84%
“…In studies assessing the association between polyphenol consumption and the risk of GDM, women were recruited from hospitals [ 24 , 26 , 27 , 30 , 31 ] or national cohort studies [ 25 , 28 , 29 ]. In articles assessing the risk of PE, three studies were hospital or care practices based [ 20 , 21 , 22 ] and one was a national cohort study [ 23 ]. Age and body mass index (BMI) of the participants in each article are shown by exposure, or by group of women affected ( Table 1 and Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation of the association of polyphenol-rich food consumption during pregnancy and PE risk was based in only four studies that met the eligibility criteria [ 20 , 21 , 22 , 23 ]. Triche and co-authors [ 20 ] compared low consumption of polyphenol-rich foods vs. high consumption, whereas the other three articles compared no consumption with high consumption to estimate PE risk [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of HbA1c at a nondiabetic level [ 57 ], both lower and higher Na intake before pregnancy [ 58 ], elevated serum IgE levels during the first trimester [ 59 ], higher caffeine intake [ 60 ], working a schedule of ≥36 h per week with night shifts [ 61 ], smoking [ 62 ], alcohol consumption [ 63 ], and becoming pregnant with in vitro fertilization and embryo transfer [ 64 ] were associated with the risk of hypertensive disorders of pregnancy. Moreover, coffee intake was associated with a decreased risk of HDP [ 60 ]. Although this is a large cohort study, some studies reported that no association between the exposures and outcomes can be found, such as calcium intake and HDP among primiparas [ 65 ].…”
Section: Prediction Prevention and Treatmentmentioning
confidence: 99%